Re-assessing political, social and economic determinants of economic growth: An analysis from selected Asian developing economies / Saima Sarwar and Noor ul Haq. - Sarwar, Saima; Haq, Noor ul (Universiti Teknologi MARA Selangor, 2017)
This study aimed to reassess the impact of different political, social and economic determinants of the economic growth in selected Asian developing economies. The variables which are being used in this regard are gross domestic product, government spending, democracy, economic freedom, foreign direct investment, primary education, labour participation and life expectancy at birth. According to the estimated results from fixed effect model, it has been found that political factors are affecting more to the economic performance of these nations as compared to the other dimensions i.e. social and economic determinants. Both sizes of bureaucracy and democracy are positively related with economic growth supporting ‘Webrian theory’ of bureaucracy. Moreover, when discussing each variable, findings shed light on this fact that in these nations except corruption, FDI, Trade openness, economic freedom, life expectancy, primary education and employment rate are positively related with GDP.